2022
DOI: 10.1007/s11523-022-00906-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FGFR2 Alterations on Overall and Progression-Free Survival in Patients Receiving Systemic Therapy for Intrahepatic Cholangiocarcinoma

Abstract: Background First-line standard-of-care therapy for advanced cholangiocarcinoma is gemcitabine plus cisplatin; there is no established second-line systemic therapy. Fibroblast growth factor receptor (FGFR)-2 fusions/rearrangements can be oncogenic drivers, occurring almost exclusively in intrahepatic cholangiocarcinoma, but little is known about whether FGFR2 status affects the response to systemic chemotherapy. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Another important question is to rule out whether the presence of FGFR alteration could affect response to systemic therapies. Several trials agree that there is not impact on response to first-line chemotherapy ( 18 , 19 ). However, this is less clear for further lines of treatment, with one trial suggesting a slightly longer PFS for second-line chemotherapy, although with the strong bias of a retrospective descriptive analysis only ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another important question is to rule out whether the presence of FGFR alteration could affect response to systemic therapies. Several trials agree that there is not impact on response to first-line chemotherapy ( 18 , 19 ). However, this is less clear for further lines of treatment, with one trial suggesting a slightly longer PFS for second-line chemotherapy, although with the strong bias of a retrospective descriptive analysis only ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several trials agree that there is not impact on response to first-line chemotherapy ( 18 , 19 ). However, this is less clear for further lines of treatment, with one trial suggesting a slightly longer PFS for second-line chemotherapy, although with the strong bias of a retrospective descriptive analysis only ( 19 ). Regarding the effect of FGFR target therapies on OS, two trials confirmed the positive prognostic role of FGFR alterations on their subset of patients, even after censoring those who had received targeted drugs ( 16 , 17 ), thus suggesting that the prognostic role of these molecular changes could be independent to the administered targeted treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the studies carried out so far, it is believed that lesions positive for EGFR, ERBB2 or KRAS mutations in their cells are associated with a more aggressive course of the disease, which obviously worsens the prognosis of patients [6]. One of the most recent discoveries, which may be of great importance in iCCA-targeted therapies, is genetic FGFR2-G3BP2 fusion [11][12][13]. This is why, now, due to the identification of numerous genetic abnormalities in iCCA cells, there are many potential opportunities for the use of new drug molecules that remain in clinical trials (pemigatinib, futibatinib or ivosidenib) [1,7,12].…”
mentioning
confidence: 99%